What is the mission of innovation?—Lexical structure, sentiment analysis, and cosine similarity of mission statements of research-knowledge intensive institutions (2022)
Mission statements (henceforth: missions) are strategic planning communication tools used by all types of organizations worldwide. Missions communicate an organization’s purpose, values, standards, and strategy. Research on missions has been prolific over the past 30 years, nevertheless several empirical gaps remain, such as single sector or country studies and restricted mission samples. In this article, we identify similarities and differences in the content of missions from government, private, higher education, and health research-knowl edge intensive institutions in a sample of 1,900+ institutions from 89 countries through the deployment of sentiment analysis, readability, and lexical diversity; semantic networks; and a similarity computation between document corpus. We found that missions of research knowledge intensive institutions are challenging to read texts with lower lexical diversity that favors positive rather than negative words. In stark contrast to this, the non-profit sector is consonant in multiple dimensions in its use of Corporate Social Responsibility jargon. The lexical appearance of ‘research’ in the missions varies according to mission sectorial con text, and each sector has a cluster-specific focus. Utilizing the mission as a strategic plan ning tool in higher-income regions might serve to explain corpora similarities shared by sectors and continents. Furthermore, our open-access dataset on missions worldwide can be used as a source for further replication, triangulation, or crowdsourcing-data studies. Also, practitioners could use our open-access dataset and insights to facilitate strategic planning activities in organizations from multiple sectors.